Ibnu Taimiyah’s Thoughts Relevance to the Constitutional Court Decision No. 46/2012 on the Illegitimate Children Lineage - Amri Amir; Rahmi Wiza; Ibrahim bin Salem Al-Saedy (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
The societal perception of illegitimate children often carries negative connotations, despite their entitlement to clear legal rights. One of the classical scholars, Ibn Taimiyah, offers distinct perspectives on the lineage and rights of children born outside of marriage, aligning with the principles laid out in Constitutional Court Decision No. 46/2012. This study aims to analyze Ibn Taimiyah's viewpoints regarding the lineage and civil rights of illegitimate children, while also examining their relevance to the aforementioned court decision. Employing a descriptive analysis method with a literature review approach, this research draws primarily from Ibn Taimiyah's seminal work, "Majmu' al-Fatawa," alongside secondary sources from journals and relevant websites. The findings underscore the alignment between Constitutional Court Decision No. 46/2012 and Ibn Taimiyah's stance on the civil rights of illegitimate children. While both recognize the child's connection to the biological mother and her family, the Court's decision extends this recognition to include the biological father and his family without the conditions of a valid marriage. In contrast, Ibn Taimiyah's perspective offers these rights in a detailed manner, contingent upon specific conditions, as children born from adultery do not stem from a legally sanctioned marriage. Ultimately, this research concludes that illegitimate children should enjoy nearly equivalent civil rights as children born within conventional marriages, as stipulated by both Ibn Taimiyah's nuanced approach and the progressive stance of Constitutional Court Decision No. 46/2012.